KAJIAN PENANGANAN GENANGAN AIR DENGAN SISTEM POLDER PADA WILAYAH PEMUKIMAN DI KOTA PONTIANAK - Zainal Wahyu; Muji Listyo Widodo (Fakultas Teknik Universitas Panca Bhakti, 2022)
The development of residential development in the city of Pontianak is growing rapidly. Changes in land use to residential areas will reduce the rainwater catchment area. One of the residential areas that often experiences inundation due to rain runoff is the Sunrise Residence Housing. The problem of standing water becomes more difficult to overcome because the existing drainage channels are not able to drain runoff water by gravity. An alternative drainage system is needed to solve the problem of standing water, especially in residential areas. To overcome the above problems, it is necessary to conduct research on the handling of runoff water that occurs especially in residential areas. In this study, the hydrological analysis method used in calculating the probability distribution uses the Log-Pearson III distribution method. The distribution test uses the Chi Square Test method. Calculation of rainfall intensity using the Mononobe method. Meanwhile, for the hydraulic analysis of the maximum discharge calculation, the Rational method is used. The purpose of this study is to control runoff when it rains with a polder drainage system in residential areas. The results of this study are the Sunrise Residence Housing Area has an area of 2.192 Ha, the maximum discharge / flood discharge planned for a 5 year return period Q = 0.003 m3/s, with an average soil permeability coefficient of 0.00000036 cm/s. If there is a rain duration of 5 hours, the volume of the retention pond in the constructed polder drainage system must be able to accommodate water with a minimum capacity of 54.0 m3.The application of the polder system can be built on the Parit Tokaya outlet channel. The polder system is one of the engineering alternatives that are considered appropriate and effective to control floods and support the development of urban areas.